2(8+2k)=-5(k+4)

Simple and best practice solution for 2(8+2k)=-5(k+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(8+2k)=-5(k+4) equation:


Simplifying
2(8 + 2k) = -5(k + 4)
(8 * 2 + 2k * 2) = -5(k + 4)
(16 + 4k) = -5(k + 4)

Reorder the terms:
16 + 4k = -5(4 + k)
16 + 4k = (4 * -5 + k * -5)
16 + 4k = (-20 + -5k)

Solving
16 + 4k = -20 + -5k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '5k' to each side of the equation.
16 + 4k + 5k = -20 + -5k + 5k

Combine like terms: 4k + 5k = 9k
16 + 9k = -20 + -5k + 5k

Combine like terms: -5k + 5k = 0
16 + 9k = -20 + 0
16 + 9k = -20

Add '-16' to each side of the equation.
16 + -16 + 9k = -20 + -16

Combine like terms: 16 + -16 = 0
0 + 9k = -20 + -16
9k = -20 + -16

Combine like terms: -20 + -16 = -36
9k = -36

Divide each side by '9'.
k = -4

Simplifying
k = -4

See similar equations:

| 2x+13=-47-8x | | 4(y-7)=2(2y-14) | | 2(8+2k)=5(k+4) | | 5d=8d-36 | | 6*2+(-6)= | | 6*3+(-12)= | | 3n=36-5n | | 4(v-6)-6v=-6 | | 2a-3b=23 | | x^2+3-x=46 | | x^2=46 | | 2x^10=123 | | x^4=64 | | x^2-x=64 | | x^2-2x=64 | | x^2-5x=64 | | 3b-67=34b-89 | | x*2+97=x*9-8 | | x*2+97=x+9-8 | | 57-7x=11x+17 | | 11-8x=171-36x | | 3x+5=-39-8x | | 4+11x=54+x | | 5x+79=11x+13 | | 2x^2-4x-320=0 | | 5x+37=15x-83 | | 11x-18=8x+3 | | 3n-12=12 | | 4n+10=26 | | P=120+3Q | | P=240-Q | | 5x+45=x+65 |

Equations solver categories